Protocol for Local On-Site Dialysate Production for Continuous Renal Replacement Therapy during the COVID-19 Pandemic. Issue 7 (29th July 2021) - Moses, Andrew A.; Stevens, Jacob S.; Fine, Derek; Carrera, Robert; Li, Alina; Parikh, Chirag R.; Mohan, Sumit
Abstract: Key Points: Because dialysate production in a hospital is not commonly performed, the technique has not been generalized to commonly available materials. On-site dialysate production may be necessary when demand is high, as it was during the coronavirus disease 2019 pandemic. This technique can be easily and widely applied to most hospitals using commonly available materials. AKI frequently occurs in patients with COVID-19, and kidney injury severe enough to require RRT is a common complication among patients who are critically ill. During the surge of the pandemic, there was a high demand for dialysate for continuous RRT, and this increase in demand, coupled with vulnerabilities in the supply chain, necessitated alternative approaches, including internal production of dialysate. Using a standard hemodialysis machine and off-the-shelf supplies, as per Food and Drug Administration guidelines, we developed a method for on-site dialysate production that is adaptable and can be used to fill multiple bags at once. The use of a central reverse osmosis unit, dedicated hemodialysis machine, sterile bags with separate ports for fill and use, and frequent testing will ensure stability, sterility, and—therefore—safety of the produced dialysate. The dialysate made in house was tested and it showed both stability and sterility for at least 30 hours. This detailed description of our process for generating dialysate can serve as a guide for other programs experiencing similar vulnerabilities in the demand versus supply of dialysate.